Jumu Al-Takstir Baina Al-Qillah Wa Al-Katsrah Fi Al-Haql Al-Ijtimaiyah Fi Al-Quran Al-Karim:Dirahsah Fi Al-Binyah Wa Al-Dilalah - Putra, Alfan; Mustafa, Mustafa (Institut Agama Islam Negeri (IAIN) Palopo, 2022)
Linguists say that there are special weights for the plural, some of which indicate the scarcity, and the other part is specific to the indication of abundance. Some of them believe that the sign of numerical paucity is limited to three to ten, and that the sign of numerical abundance is confined to three to infinity. Some of them believe that the meaning of the few is limited to between three to ten, while the abundance is limited to its numerical significance between what is above ten indefinitely. Accordingly, the study aims to know the number of plurals of few versus many in the field of social relations in the Holy Qur’an, showing their linguistic significance, as well as knowing the divisions of these plurals according to their grammatical structure. Depending on the descriptive analytical approach, the results show that the multiplicity, the few, and the many in the field of social relations in the Holy Qur’an were divided into four weights. And that the plural has changed its wording or appraisal, and among its forms is what has been done with an increase, and some of it has been changed with a decrease, and some of it has been changed its form, and some of it has been done with a decrease and a change of form, and some of it has been done with an increase, a decrease and a change combined, and that this change some of them indicates the lack and the other section is concerned with the significance over abundance. Keywords: plural multiplicity, plural of few, plural of many, social relations in the Qur'an.